Administrative Discretion and Maladministration in Fixed Asset Management of Community Health Centers: A Comparative Study of Left-Behind and Non-Left-Behind Regions - Vera Yuliyanti; Mastur Mastur; Mursito Mursito (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
His study aims to analyze the practice of administrative discretion and its potential for maladministration in the management of fixed assets at Public Service Agency Regional Units (BLUD) Community Health Centers (Puskesmas), with a comparative focus on disadvantaged and non-disadvantaged areas in Bulungan Regency, Indonesia. The study addresses the legal and administrative challenges arising from the interaction between the financial flexibility granted to BLUDs and the mandatory compliance with regional asset management regulations. A qualitative approach with a comparative design and an empirical juridical perspective was employed to examine the implementation of the regulatory framework in actual administrative practice. Data were collected through semi-structured interviews, direct observation, and document analysis involving heads of Puskesmas, BLUD treasurers, asset officers, the Regional Financial and Asset Management Agency (BKAD), the District Health Office, and the Audit Board of Indonesia (BPK). Data were analyzed using qualitative techniques consisting of data reduction, data display, thematic categorization, comparative analysis, and conclusion drawing, supported by source and method triangulation. The findings indicate that administrative discretion is primarily exercised to ensure the continuity of healthcare services under geographical, infrastructural, and human resource constraints rather than to circumvent legal provisions. The risk of maladministration is predominantly associated with administrative limitations, including delayed inventory updates, inadequate asset documentation, and limited technical capacity, rather than abuse of authority. The study further reveals that the application of discretion differs between disadvantaged and non-disadvantaged areas due to contextual operational conditions. The novelty of this research lies in demonstrating that contextual administrative discretion, when exercised in good faith, properly documented, and supported by institutional supervision, constitutes an adaptive governance mechanism that promotes legal certainty, accountability, and continuity of public healthcare services without necessarily leading to maladministration.